2022
DOI: 10.3389/fcvm.2022.924461
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 in coronary artery disease: Clinical biomarkers and treatment guidance

Abstract: The IL-33/ST2 L signaling pathway is involved in the pathophysiological processes of several diseases and mainly exerts anti-inflammatory and antifibrotic effects. Soluble suppression of tumorigenicity 2 (sST2), which serves as a competitive inhibitory molecule of this pathway, is a member of the interleukin (IL)-1 family, a decoy receptor for IL33, thought to play a role in cardiac remodeling and the inflammatory process. However, the association between sST2 and coronary artery disease (CAD), one of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…However, some of our patients may have had more severe gastritis than others, or even subtle symptoms. Unfortunately, we do not have this data.sST2 is a biomarker that has been extensively studied in recent years [ 7 9 ]. An association between sST2 and mortality has already been demonstrated in several populations [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of our patients may have had more severe gastritis than others, or even subtle symptoms. Unfortunately, we do not have this data.sST2 is a biomarker that has been extensively studied in recent years [ 7 9 ]. An association between sST2 and mortality has already been demonstrated in several populations [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble suppression of tumorigenicity-2 (sST2) is a biomarker that has been extensively studied in recent years [ 7 9 ]. It is a member of the interleukin-1 receptor family [ 10 ] and is secreted in response to various forms of cellular stress, including inflammation, tissue injury, and mechanical strain [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of studies have shown that the increase of circulating sST2 is of great signi cance in the diagnosis and prognosis of myocardial infarction, hypertension, diabetes, pulmonary hypertension, myocardial hypertrophy and heart failure, the understanding of IL33/ST2 in the cardiovascular eld is still controversial. In particular, there are completely different views on the pathophysiological role of cardiomyocytes [10][11][12][13][14][15]. RND3, also known as RhoE, is a member of the Rho GTP protein superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that recombinant sST2 promotes mitochondrial fusion in human cardiac broblasts, increasing oxidative stress and the secretion of in ammatory cytokines [11]. High levels of sST2 have been found to be associated with poor prognosis of cardiac brosis and cardiomyopathy, which can be used as an independent predictor of heart disease [12][13][14].…”
Section: Introductionmentioning
confidence: 99%